Acculturation of Malay culture into Malaysian non-malay and non-Malaysian and its reflection on the neural substrate of culture specific emotion - Samsuri, Norlyiana (2024)
Racism, prejudice, and discrimination are significant issues that can arise from cultural diversity. It is important to understand the effect of acculturation across members of different cultural groups and how this interaction displays cultural similarities. This research aims to understand the influence of acculturation of majority culture (Malay) into Malaysian non-Malay (Chinese and Indian) and non-Malaysian participants on the neural process of culturally specific emotion. This research was implemented in two phases: (1) Validation study, and (2) Event Related Potential (ERP) study. The amplitude and latency of ERP components were analyed using SPANOVA. The source of localisation and connectivity were analysed using narrative analysis. For the active paradigm, the interaction effect analysis showed significant activation in the Temporal area (T6) of the amplitude of P200 [F (5.378, 207.932) =2.245, p = 0.047], N200 [F (5.798, 224.177) =2.727, p = 0.015], and P300 [F (5.830, 225.432) =3.676, p = 0.002] ERP components. The source of localisation for Malay participants indicated patterns originated in Temporal lobe for N100 and Occipital lobe for P300, sharing similar patterns with non-Malay and non-Malaysian participants living in Malaysia for less than one year. There were 21 connectivity activations in Malay participants, with shared similarities in sensory, motor, visual, memory, emotion, attention, and decision-making processes among non-Malay participants, followed by non-Malaysian participants living in Malaysia for more than one year. For the passive paradigm, the interaction effect analysis showed significant activation in the Parietal-Temporal-Occipital area of the latency T4 [F (8.896, 343.974) = 2.336, p = 0.015], O2 [F (9, 348) =2.446, p = 0.010] of N100 and P4 [F (9, 348) = 2.546, p = 0.008], O1 [F (9, 348) = 2.355, p = 0.014] of P300 ERP components. The source of localisation for Malay participants indicated pattern originated in Occipital lobe in N100 and Frontal lobe in P200, shared similar pattern with non-Malay and non-Malaysian participants living in Malaysia for more than one year. There were 17 connectivity activations in Malay participants with shared similarities in sensory, motor, visual, memory, emotion, language, and higher cognitive functions among non-Malay participants, followed by non-Malaysian participants living in Malaysia for more than one year, and non-Malaysian participants living in Malaysia for less than one year. In conclusion, the finding of this research indicates that non-Malay participants share similar neural process pattern associated with culturally specific emotion with Malay participants due to the influence of acculturation.